SpO2 and Heart Rate During a Real Hike at Altitude Are Significantly Different than at Its Simulation in Normobaric Hypoxia - Netzer, Nikolaus C.; Rausch, Linda; Eliasson, Arn H.; Gatterer, Hannes; Friess, Matthias; Burtscher, Martin; Pramsohler, Stephan (Frontiers in Physiology, 2017)
Rationale: Exposures to simulated altitude (normobaric hypoxia, NH) are frequently used in preparation for mountaineering activities at real altitude (hypobaric hypoxia, HH). However, physiological responses to exercise in NH and HH may differ. Unfortunately clinically useful information on such differences is largely lacking. This study therefore compared exercise responses between a simulated hike on a treadmill in NH and a similar field hike in HH. Methods: Six subjects (4 men) participated in two trials, one in a NH chamber and a second in HH at an altitude of 4205 meters on the mountain Mauna Kea. Subjects hiked in each setting for 7 hours including breaks. In NH, hiking was simulated by walking on a treadmill. To achieve maximal similarity between hikes subjects used the same nutrition, clothes and gear weight. Measurements of peripheral oxygen saturation (SpO2), heart rate (HR) and barometrical pressure (PB)/inspired oxygen fraction (FiO2) were taken every 15 minutes. Acute mountain sickness (AMS) symptoms were assessed using the Lake-Louise-Score at altitudes of 2800, 3500 and 4200 meters. Results: Mean SpO2 values of 85.8% in NH were significantly higher compared to those of 80.2% in HH (p=0.027). Mean HR values of 103 bpm in NH were significantly lower than those of 121 bpm in HH (p=0.029). AMS scores did not differ significantly between the two conditions. Conclusion: Physiological responses to exercise recorded in NH are different from those provoked by HH. These findings are of clinical importance for subjects using simulated altitude to prepare for activity at real altitude. Trial registration: Registration at DRKS. (Approval No. 359/12, Trial No. DRKS00005241).